2002
DOI: 10.1101/gad.948702
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPα induces adipogenesis through PPARγ: a unified pathway

Abstract: PPAR␥ and C/EBP␣ are critical transcription factors in adipogenesis, but the precise role of these proteins has been difficult to ascertain because they positively regulate each other's expression. Questions remain about whether these factors operate independently in separate, parallel pathways of differentiation, or whether a single pathway exists. PPAR␥ can promote adipogenesis in C/EBP␣-deficient cells, but the converse has not been tested. We have created an immortalized line of fibroblasts lacking PPAR␥, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

43
952
2
14

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,306 publications
(1,011 citation statements)
references
References 21 publications
43
952
2
14
Order By: Relevance
“…The total number of circulating vascular progenitor cells may also be dependent on testosterone levels [45]. Regulation of progenitor cell differentiation is a complex process, dependent on numerous hormones, growth factors, and specific activation of a cascade of gene expression [42,[46][47][48][49][50][51].Critical regulators of adipocyte differentiation include C/EBPα (CCAAT/enhancer binding protein), PPARγ2 (peroxisome proliferator-activated receptor), and LPL (lipoprotein lipase) [47,48,[52][53][54][55][56][57]. Alternatively, transdifferentiation of smooth muscle cells into other phenotypes may occur [58][59][60][61].…”
Section: Testosterone Regulates Cellular Growth and Differentiationmentioning
confidence: 99%
“…The total number of circulating vascular progenitor cells may also be dependent on testosterone levels [45]. Regulation of progenitor cell differentiation is a complex process, dependent on numerous hormones, growth factors, and specific activation of a cascade of gene expression [42,[46][47][48][49][50][51].Critical regulators of adipocyte differentiation include C/EBPα (CCAAT/enhancer binding protein), PPARγ2 (peroxisome proliferator-activated receptor), and LPL (lipoprotein lipase) [47,48,[52][53][54][55][56][57]. Alternatively, transdifferentiation of smooth muscle cells into other phenotypes may occur [58][59][60][61].…”
Section: Testosterone Regulates Cellular Growth and Differentiationmentioning
confidence: 99%
“…5,6 PPARg and C/EBPa induce each other's expression through a positive feedback loop. 7 The latter factors drive the expression of genes that are necessary for lipid synthesis. C/EBPa is required for induction and maintenance of PPARg levels.…”
Section: Introductionmentioning
confidence: 99%
“…C/EBPa is also involved in the regulation of insulin sensitivity. 7 PPARg exists as two protein isoforms: PPARg1 that is found in fat cells and is present at lower levels in a variety of cells types, and PPARg2 that is adipocyte-specific. 8 PPARg was shown to induce adipogenesis, 9 and a number of adipocyte genes.…”
Section: Introductionmentioning
confidence: 99%
“…For the past decades, in vitro preadipocyte cell lines such as 3T3-L1 have been extensively used to define genes central the adipocyte phenotype [16,17]. A variety of in vitro and in vivo studies have determined that the peroxisome proliferator-activated receptor γ (PPAR γ ) a member of the ligand activated steroid hormone receptor family, is a master transcriptional regulator of the adipogenic program [15,41,[55][56][57]80], and has also illustrated the important contribution of the CCAAT/enhancer-binding protein (C/EBP) family of transcriptional regulators to adipogenesis [2,58,72,79,80]. However, recent intensive dissection of the adipocyte transcriptome by DNA oligonucleotide microarrays and other approaches has revealed that a number of additional signaling networks and protein families are likely involved in the regulation and/or maintenance of adipocyte differentiation and function [39,43,59,64].…”
Section: Introductionmentioning
confidence: 99%